Evaluation Model of the Regional Economic Vitality. (May 2020) - Hu, Jinyan; Cai, Yongfang; Cheng, Jiaming
Abstract: Regional economic vitality is an important part of regional comprehensive competitiveness. Accurate assessment of regional economic vitality can reflect the state of economic development among different regions and provide reference to the developing policies of regional economic. To measure the regional economic vitality of main Chinese cities, in this paper, we first establish a mathematical index system based on five aspects (i.e., industrial vitality, capital vitality, innovation vitality, talent vitality and humanistic vitality). Then, the evaluation model of regional economic vitality is constructed using entropy method. The result shows that among 19 main cities of China, Guangzhou and Hangzhou have the highest economic vitality in the first-tier and second-tier cities, respectively. Besides, the change of the comprehensive evaluation of economic vitality among the first-tier cities is more obvious than that between second-tier cities. The evaluation results reflect regional differences in Chinese economic development and can provide valuable reference for exploring benign sustainable policies for regional economic development.